2018
DOI: 10.12788/ajo.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Total Shoulder Arthroplasty Using a Bone-Sparing, Precision Multiplanar Humeral Prosthesis

Abstract: Proper reconstruction of proximal humeral anatomy is of primary importance to maximize patient outcomes after total shoulder arthroplasty. This article describes a new arthroplasty technique, where a fixed multiplanar bone resection is made and a novel implant, which is designed to precisely match the bone resection, is inserted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We previously reported on this technique as being reliable in replicating the preoperative anatomy and center of rotation in both a cadaveric specimen and in clinical practice. 3,17,18 The mean patient age in this group was 73 years, which is older than the groups studied by Habermeyer, Egger, Churchill, and Berth, where the mean ages were 58, 59, 66, and 67 years, respectively. 6,13,15,20 In those studies, nonstemmed arthroplasty was shown to have very low rates of loosening over time.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We previously reported on this technique as being reliable in replicating the preoperative anatomy and center of rotation in both a cadaveric specimen and in clinical practice. 3,17,18 The mean patient age in this group was 73 years, which is older than the groups studied by Habermeyer, Egger, Churchill, and Berth, where the mean ages were 58, 59, 66, and 67 years, respectively. 6,13,15,20 In those studies, nonstemmed arthroplasty was shown to have very low rates of loosening over time.…”
Section: Discussionmentioning
confidence: 50%
“…This technique has been demonstrated in cadaveric and radiographic studies to be highly accurate in replicating the preoperative anatomy. 3,18 The design was inspired by the femoral component in total knee arthroplasty, which rests on dense bone just below the subchondral surface and demonstrates excellent longevity in patients over a wide age range in numerous long-term studies. 2,36,45 In order to address potential challenges encountered with a more conservative bone resection, a glenoid component with angled anchoring pegs that can be inserted from an oblique angle, in the direction of a deltopectoral incision, was developed.…”
mentioning
confidence: 99%
“…The cutting guides and surgical technique were designed to match the amount of bone resected to the thickness of the humeral head implant and were specifically developed to address the problem of inconsistency in humeral head reconstruction. 27 Minimizing the amount of bony resection during humeral head preparation has a number of benefits including improved implant fixation in the dense subchondral bone of the anatomic neck 28 and preservation of proximal bone stock in the case of revision surgery. 19 Additionally, proper positioning of the implant at the native center of the articular surface is facilitated when there is no stem affecting placement.…”
Section: Discussionmentioning
confidence: 99%